Quality of life in the Iranian Blind War Survivors in 2007: a cross-sectional study - Amini Reza; Haghani Hamid; Masoumi Mehdi (BMC, 2010)
Abstract Background Quality of Life measurements are necessary tools for effectively evaluating health services. In the population of patients afflicted with war-related blindness in Iran, such measurements have yet to be documented and utilized. "The design and implementation of this study involved the determination of a baseline score for QOL in a population of Iranian blinded in the Iraq-Iran war in order to facilitate the design of interventions intended to improve the population's QOL." Methods This was a cross-sectional study of a representative population of 250 war victims blind in both eyes at a 14-day recreational conference. Results Participants had a mean age of 43.20(SD8.34) and their composition was 96.5% male and 3.5% female with a mean SF-36 QOL score of 59.20(SD22.80). An increasing level of education among the participants correlated with a higher QOL score (p = 0.006). The QOL also has a significant correlation to number of injuries (p < 0.0001). High systolic and diastolic blood pressure, hearing loss, and tinnitus had negative individual correlations to QOL (p = 0.016, 0.016, 0.005, p < 0.0001). The male sexual disorders of erectile dysfunction and premature ejaculation both had significant correlations to QOL (p = 0.026, p < 0.0001). Hypercholesterolemia showed significant correlation to QOL (p = 0.021). Conclusions As blind war survivors' age, they will present with a greater set of burdens despite their relatively better QOL in the physical component scale when compared with lower limb amputees. Risk factors of cardiovascular attack such as high blood pressure and hypercholesterolemia were present and need future interventions. Key words Quality of life, blindness, SF36, health